PROMOTING EFL STUDENTS ENTREPRENEURSHIP ENTHUSIASM: USING PROJECT-BASED LEARNING IN EXTENSIVE READING ACTIVITIES - Zulfariati, Zulfariati (ELP (Journal of English Language Pedagogy), 2023)
This article discusses how Extensive Reading (ER) activities promote English as a Foreign Language (EFL) college students’ entrepreneurship enthusiasm by giving the chance to the individual student to select the topic to be read based on the most interesting one in his/her life. As ER is defined as pleasure reading, most of the previous research reports promoting ER activities for EFL students deal mostly with reading literary texts. For EFL college students, however, ER should not focus on reading literary texts, but also on the academic and popular ones. They need to be able to read a wide range of academic and popular texts for school task demands and for their prospective work purpose. They should be encouraged to read other types of texts other than literary one—which can improve their entrepreneurship enthusiasm. The method used in this study is classroom action research by implementing Project Based Learning (PBL) in two cycles. The results of this study showed that in the first cycle the students were able to read everything about the most interesting thing in their life guided by the mind map usage, made papers of reading reports based on both printed and digital resources, made the slides of oral report contained project plan of entrepreneurship products or services. In the second cycle the students were able to complete the project in form of portfolio contained the complete plan of entrepreneurship products and/or services. It is concluded that the implementing of PBL can promote EFL students’ entrepreneurship enthusiasm.